DAMPAK AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BEI SELAMA TAHUN 2006 - 2012) - Vincensius Hendy Septiawan, 09.05.51.0100 (Students Journal of Economic and Management, 2013)
The purpose of this study is to examine whether there are differences financial performance before and after the acquisition of the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2006-2012. In this study population taking companies listed on the Indonesia Stock Exchange in the period 2006 - 2012, based on the population by sampling using purposive sampling method obtained a sample of 30 samples. Based on the research that has been done so knowable There are differences Return On Asset (ROA) before and after the acquisition. There were no differences Return On Equity (ROE) before and after the acquisition. There was no difference Current Ratio (CR) before and after the acquisition. There are differences Earning Per Share (EPS) before and after the acquisition. There was no difference in Total Assets Turn Over (TATO) before and after the acquisition. Keyword : Return On Asset (ROA), Return On Equity (ROE), Current Ratio (CR), Earning Per Share (EPS) and Total Assets Turn Over (TATO)